The conserved brassinosteroid-related transcription factor BIM1a negatively regulates fruit growth in tomato - Mori, Kentaro; Lemaire-Chamley, Martine; Jorly, Joana; Carrari, Fernando; Conte, Mariana; Asamizu, Erika; Mizoguchi, Tsuyoshi; Ezura, Hiroshi; Rothan, Christophe (Oxford University Press, 2021)
Brassinosteroids (BRs) are steroid hormones that play key roles in plant development and defense. Our goal is to harness the extensive knowledge of the Arabidopsis BR signaling network to improve productivity in crop species. This first requires identifying components of the conserved network and their function in the target species. Here, we investigated the function of SlBIM1a, the closest tomato homolog of AtBIM1, which is highly expressed in fruit. SlBIM1a-overexpressing lines displayed severe plant and fruit dwarfism, and histological characterization of different transgenic lines revealed that SlBIM1a expression negatively correlated with fruit pericarp cell size, resulting in fruit size modifications. These growth phenotypes were in contrast to those found in Arabidopsis, and this was confirmed by the reciprocal ectopic expression of SlBIM1a/b in Arabidopsis and of AtBIM1 in tomato. These results determined that BIM1 function depends more on the recipient species than on its primary sequence. Yeast two-hybrid interaction studies and transcriptomic analyses of SlBIM1a-overexpressing fruit further suggested that SlBIM1a acts through its interaction with SlBZH1 to govern the transcriptional regulation of growth-related BR target genes. Together, these results suggest that SlBIM1a is a negative regulator of pericarp cell expansion, possibly at the crossroads with auxin and light signaling.